Radical business : how to transform your organization in the age of global crisis - Davis, John A. (Emerald Publishing Limited, 2022)
We live in an age of global crises, from spiralling income inequality to the climate emergency. Businesses have been major contributors to the problems we face, but they are also uniquely well-placed to effect positive change. So what can businesses do to shift from being a makers of goods to a force for good? In Radical Business, John Davis argues the changes needed are surprisingly simple. The difficulty lies in the effort to change human behavior and to dismantle decades of investment that reinforces obsolete practices. He offers examples of companies that are already taking action and presents a simple framework to help C-suite leaders and executive teams develop their own blueprint for putting societal value at the heart of their business.; We can no longer ignore that established ways of doing business pose real existential threats to humankind. We cannot change what has occurred, but we can change how we do things from now on.